Produksi dan Uji Aktivitas Enzim Selulase dari Bakteri Bacillus subtilis - Al Maratun Sholihati; Maswati Baharuddin; Santi Santi (Al-Kimia, 2015)
Enzyme cellulose can be produced from bacteria Bacillus subtilis. This bacteria is a kind of bacteria which grounded on the genus that can degrade cellulose to glucose. Cellulase enzyme acquired different optimum pH and temperature depends on the bacteria. This research aim to produce and analyze the activity of the cellulose enzyme from bacteria Bacillus subtilis at optimum pH and temperature. The research of this enzyme cellulose derived by prolific process and rejuvenation  bacteria Bacillus subtilis on the nutrition culture, nutrition selective, and nutrition production that executed by cold centrifugation to obtain extract or the enzyme cellulose at the temperature of 4°C, 3500 rpm within 15 minutes. On the determine pH with variety pH 5,6 using buffer acetat and pH 6,0; 6,5; 7,0; 7,5; and 8.0 using phosphate buffer while on the determine temperature using variety temperature 25°C, 30°C, 35°C, 40°C, 45°C, and 50°C which the next make an experiment activity enzyme cellulose by method Nelson-Somogy that measured in spectrophotometer UV-Vis of λ 540 nm. The result shows that the highest enzyme activity at optimum pH of 6, 0 is 4,3661 10ˉ3 U/mL and in optimum temperature of 30°C as is 5,6609 10ˉ3 U/mL.